Rhetoric and reality : gender and the colonial experience in South Asia - Powell, Avril A. (Avril Ann); Lambert-Hurley, Siobhan (SOAS studies on South Asia, 2006)
Contributed articles presented at a workshop held in Dhaka, December 2002 on gender identity and family life of Indian women organised by Bangladesh Chapter of International Federation for Research in Women's History.